1991
DOI: 10.1038/jcbfm.1991.139
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of Cerebellar Fastigial Nucleus Reduces Ischemic Infarction Elicited by Middle Cerebral Artery Occlusion in Rat

Abstract: Electrical stimulation of the cerebellar fastigial nucleus (FN) globally and profoundly increases cerebral blood flow via a cholinergic mechanism. In cerebral cortex, the vasodilation is unassociated with alterations in cerebral glucose utilization, a condition favoring protection against cerebral ischemia. We sought to determine whether FN stimulation would modify the size of the focal ischemic infarction resulting from occlusion of the middle cerebral artery (MCA). The MCA was occluded in anesthetized rats o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…NO has been proposed to modulate the release of several neurotransmitters (Moncada et aI., 1989;Toda and Okamoto, 1990;Crossin, 1991), some of which may counteract the action of L-Glu. That neurotransmitter-regulated events may play a role in neuroprotection in focal cerebral infarction has been demonstrated by the observation that focal ischemic infarction elicited by occlusion of the MCA in rat may be reduced by almost 50% by excitation of intrinsic neuronal net works related to the cerebellar fastigial nucleus (Berger et a!., 1990;Reis et a!., 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NO has been proposed to modulate the release of several neurotransmitters (Moncada et aI., 1989;Toda and Okamoto, 1990;Crossin, 1991), some of which may counteract the action of L-Glu. That neurotransmitter-regulated events may play a role in neuroprotection in focal cerebral infarction has been demonstrated by the observation that focal ischemic infarction elicited by occlusion of the MCA in rat may be reduced by almost 50% by excitation of intrinsic neuronal net works related to the cerebellar fastigial nucleus (Berger et a!., 1990;Reis et a!., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The methods for preparation of rats, for instrumenta tion, for measurement of blood gases, glucose, and he matocrit (Hct), for production of focal cerebral ischemia by occlusion of the MCA, for computation of infarct vol ume, and for recording of regional CBF (rCBF) by laser Doppler flowmetry (LDF) have been described in detail in other publications from our laboratory (Iadecola and Reis, 1990;Reis et at., 1991;Maiese et ai., 1992) and will only be summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Glickstein, fastigial nucleus (FN) had play an important roles in cerebrovascular regulation. Several studies suggested that electrical stimulation of the FN could markedly elevate rCBF globally in the brain [15,16]. These studies also showed that in many brain regions including the cerebral cortex, the increase in rCBF elicited from FN stimulation was not associated with the changes of local cerebral metabolism.…”
Section: Discussionmentioning
confidence: 64%
“…In analogy with other interventions for brain protection (Choi, 1990), FN stimulation could reduce tissue damage by improving CBF to the ischemic tissue and decreasing the degree of oligemia (hemodynamic mechanism). Alternatively, FN stimulation might increase the resistance of brain cells to ischemic damage by releasing protec tive agents in the ischemic territory, possibly neu rotransmitters (cytoprotective mechanism) (Reis et al, 1991). The finding that FN stimulation increases CBF in the ischemic territory strongly suggests that the mechanism of the protection is "hemody namic."…”
Section: Discussionmentioning
confidence: 99%